2014
DOI: 10.1038/srep04133
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine absorption from electronic cigarette use: comparison between first and new-generation devices

Abstract: A wide range of electronic cigarette (EC) devices, from small cigarette-like (first-generation) to new-generation high-capacity batteries with electronic circuits that provide high energy to a refillable atomizer, are available for smokers to substitute smoking. Nicotine delivery to the bloodstream is important in determining the addictiveness of ECs, but also their efficacy as smoking substitutes. In this study, plasma nicotine levels were measured in experienced users using a first- vs. new-generation EC dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
346
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 384 publications
(372 citation statements)
references
References 25 publications
20
346
2
2
Order By: Relevance
“…Current evidence on nicotine delivery in e-cigarettes commercially available at the time of the survey suggests a much more delayed nicotine onset than with cigarettes. 47,48 These data are consistent with a large body of evidence suggesting that rapid delivery of drugs leads to increased addictive symptomatology than slower delivery. [49][50][51] However, e-cigarettes are likely to evolve into more rapid nicotine delivery systems as product design is improved, as we have already seen in comparisons between first and second generation e-cigarettes.…”
Section: E-cigarettes Versus Cigarettessupporting
confidence: 78%
“…Current evidence on nicotine delivery in e-cigarettes commercially available at the time of the survey suggests a much more delayed nicotine onset than with cigarettes. 47,48 These data are consistent with a large body of evidence suggesting that rapid delivery of drugs leads to increased addictive symptomatology than slower delivery. [49][50][51] However, e-cigarettes are likely to evolve into more rapid nicotine delivery systems as product design is improved, as we have already seen in comparisons between first and second generation e-cigarettes.…”
Section: E-cigarettes Versus Cigarettessupporting
confidence: 78%
“…Some reports suggest that ECIGs deliver a considerable amount of nicotine, 10 whereas other reports do not. 15,16,17 It has been hypothesized that these mixed results derived from variations in user experience and device type, 10,39 factors which, as this study has shown, likely affect the amount of nicotine obtained from the mouth end of an ECIG. Depending on user puff topography and operating conditions, we have found that a given ECIG product can provide far less or far more nicotine than a single combustible cigarette.…”
Section: Resultsmentioning
confidence: 99%
“…This is also consistent with existing data, showing that advanced generation models deliver higher blood nicotine levels than current "cigalike" models. 25,26 This study found that scores on the PS Electronic Cigarette Index were significantly related to the concentration of nicotine in the e-cig liquid being used, even after controlling for other predictors. This may not be very surprising, but is at least consistent with the idea that the items selected for the index are somewhat sensitive .…”
Section: (234)mentioning
confidence: 91%